Uso de membranas eletrofiadas contendo carvão ativado para remoção de poluentes - Adamczuk, Rosana Soares Santos (2023)
Concern about water quality is increasing every year due to contamination, which can occur from pharmaceutical residues, pesticides, dyes and heavy metals. Among pharmaceutical waste, antibiotics, used to control infectious diseases, are difficult to treat and often require a combination of techniques to completely remove the effluents before they are dumped into water bodies. In this context, polymeric membranes obtained through electrospinning have been used as adsorbents to remove pollutants. Thus, the present work aimed to obtain and characterize polymeric membranes using the electrospinning technique. In this way, a chitosan membrane was produced combined with poly (ethylene oxide) PEO, and another made of chitosan, PEO and activated carbon, being used in the adsorption test of the drug tetracycline hydrochloride. All membranes were cross-linked with glutaraldehyde. The membranes were characterized based on FTIR, TGA, SEM and XRD analyses, through these analyzes it was possible to verify that the addition of activated carbon did not change the characteristics of the membrane. The zero charge point test was performed on the membrane containing activated carbon in order to verify the charges on the surface. The adsorption experiments were conducted in batch, under pH 7.00, temperature 30 ºC and agitation at 150 rpm. The pseudo-second order model was the one that best fitted the adsorption kinetics data and the isotherm that best represented the equilibrium test was the Langmuir one. Finally, the chitosan/PEO/activated carbon membrane showed a maximum adsorption capacity of 2.491 ± 0.669 mg g-1 for the drug under study.